2012
DOI: 10.1590/s0101-31222012000200007
|View full text |Cite
|
Sign up to set email alerts
|

Physiological maturity of fruits and seeds of Poincianella pyramidalis (Tul.) L.P. Queiroz

Abstract: -The Leguminosae family is one of the most representative botanical families of the Caatinga, with 80 endemic species, highlighting the catingueira (Poincianella pyramidalis). The objective of this research work was to study the maturation process of P. pyramidalis seeds based on the physiological maturity. Five harvest of fruits and seeds were carried out, with 15 days interval each, in a period from July to September 2010. The harvests began 75 days after anthesis (d.a.a.) and lasted until 135 d.a.a. Fruits … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 13 publications
1
4
0
2
Order By: Relevance
“…Similar behavior was observed by Lima et al (2012) who verified that the maximum dry biomass and seedling length of Poincianella pyramidalis [(Tul.) L. P. Queiroz] coincided with the moment that the seeds also had the highest germination speed index.…”
Section: Seedling Performancesupporting
confidence: 84%
“…Similar behavior was observed by Lima et al (2012) who verified that the maximum dry biomass and seedling length of Poincianella pyramidalis [(Tul.) L. P. Queiroz] coincided with the moment that the seeds also had the highest germination speed index.…”
Section: Seedling Performancesupporting
confidence: 84%
“…At site 1, seedlings with greater accumulation of dry matter were obtained from the stage when the fruits were orange color and with greater length from yellow fruits (Table 3). Lima et al (2012) have found that the maximum dry matter content and length of seedlings of Poincianella pyramidalis [(Tul.) L. P. Queiroz] coincided with the time when the seeds had a higher germination speed index.…”
Section: Resultsmentioning
confidence: 99%
“…The variation between the seed physiological quality of different M. caesalpiniifolia trees in this study may be considered lower than of tree species such as Poincianella pyramidalis (Tul.) L.P. Queiroz (LIMA et al, 2014) and Sideroxylon obtusifolium (Roem. & Schult.)…”
Section: Physiological Qualitymentioning
confidence: 99%
“…High-quality seeds and technical planning are required for all production stages, starting with the selection of trees from which the seeds will be collected MEDEIROS, 2007). Therefore, seed quality control in the laboratory is necessary prior to the selection of suitable trees (LIMA et al, 2014).…”
Section: Introductionmentioning
confidence: 99%